PENGELOLAAN ARSIP MEDIA AUDIO BERITA ELEKTRONIK PADA LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA (LPP RRI) STASIUN TELANAIPURA JAMBI (Jurnal Adabiya, 2020)
This paper is a descriptive analysis which aims to manage the management of electronic news audio media archives at the Indonesian Radio Public Broadcasting Institute (LPP RRI) Telanaipura Jambi Station. Field findings show that archives are stored on CDs, hard drives, and flash drives. Archives are arranged in order of date, month and year. so far there has been no automation in the retrieval process. The obstacles in managing records are human resources and facilities. There are efforts to overcome this problem, among others, by regulating the procurement of employee recruitment and arranging the budget for managing records.
Keywords: archives; electronic media audio news